2013
DOI: 10.1071/en13128
|View full text |Cite
|
Sign up to set email alerts
|

Organic fluorine content in aqueous film forming foams (AFFFs) and biodegradation of the foam component 6 : 2 fluorotelomermercaptoalkylamido sulfonate (6 : 2 FTSAS)

Abstract: Environmental context Total organofluorine and known fluorosurfactants were quantified in 11 aqueous film forming foams (AFFFs) used to extinguish fires in Ontario, Canada, and one commercial AFFF product. By comparing the concentrations of known fluorosurfactants with the total organofluorine, less than 10% of the fluorosurfactants were identified in half of the samples. Our biodegradation experiment with one of the fluorosurfactants using waste-water treatment plant sludge showed that it was a potential sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
184
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(199 citation statements)
references
References 23 publications
11
184
2
2
Order By: Relevance
“…36 FTSA was found to be present in some AFFF formulations, and significant release levels (up to 14 600 ng/L) of 4:2, 6:2, and 8:2 FTSA were detected in groundwater where fire-training activities were conducted. 36 Degradation of fluorotelomer precursors is the primary FTSA source, 37 and the elevated abundance of 8:2 FTSA on surfacial AFFF-impacted soil further suggest contributions of the C8 FTSA-based compounds in the environment. 38 Correlations between Fluorinated Sulfonates and Influencing Factors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…36 FTSA was found to be present in some AFFF formulations, and significant release levels (up to 14 600 ng/L) of 4:2, 6:2, and 8:2 FTSA were detected in groundwater where fire-training activities were conducted. 36 Degradation of fluorotelomer precursors is the primary FTSA source, 37 and the elevated abundance of 8:2 FTSA on surfacial AFFF-impacted soil further suggest contributions of the C8 FTSA-based compounds in the environment. 38 Correlations between Fluorinated Sulfonates and Influencing Factors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The relatively high PFOS and PFHxS serum levels are likely attributable to exposure to 3M AFFF as perfluorinated sulfonates (PFSAs) have been identified as major components in 3M foam concentrates (Backe et al, 2013;Weiner et al, 2013), as well as in groundwater Table 3 Results of ANOVA for possible associations between PFAA levels and biochemical outcomes. Models for cholesterol, HDL, LDL, and triglycerides (mmol/L) based on participants with measured BMI, confirmed fasting before blood sample, and those not taking cholesterol-lowering medications (n = 17).…”
Section: Pfaa Exposure Attributed To Afff Usagementioning
confidence: 98%
“…As a reference, the 6:2 fluorotelomer thioether amido sulfonate (C 15 H 17 O 4 NS 2 F 13 À1 ) which has been identified in some AFFF formulations is 42% fluorine by weight. A 0.15-3% estimate of organic fluorine in foam concentrates is somewhat less than 5% found by Weiner et al (2013). With these assumptions, 100 mg foam concentrate/L solutions used in this study represent a minimum of 150 lg L À1 fluorine which would be within IC detection limits.…”
Section: Oxidation and Defluorination Using Fenton's Oxidationmentioning
confidence: 96%
“…Identities of surfactants in foam formulations are proprietary, however some components and degradation products have been identified (Schultz et al, 2004;Place and Field, 2012;Backe et al, 2013;D'Agostino and Mabury, 2014). Biotransformation studies of some fluorotelomers including a fluorotelomer sulfonate specifically identified in AFFFs demonstrate that one or more CF 2 groups may be sequentially removed by wastewater treatment plant microbes (Wang et al, 2005;Weiner et al, 2013). In another study, biodegradation of the perfluorinated portion of a fire fighting foam fluorotelomer did not occur (Moe et al, 2012).…”
Section: Introductionmentioning
confidence: 92%